Language's Borrowings: The Role of the Borrowed and Arabized Words in Enriching Arabic Language (American Journal of Humanities and Social Sciences, 2014)
Borrowing is entering Arabic language. Researchers focus on the origin of the borrowed words and their meanings without analyzing the syntactic and semantic changes of these words. This paper focuses on Arabic language's borrowings from other languages. Moreover, it studies the meaning of 'arabization' and the role of arabized and borrowed words in enriching Arabic language, the difference between the arabized words and the borrowed ('dakheel') ones by examining and analyzing samples for every type. Arabic words are derivatives from the base form, which is applied to "wazen", three-letter, 'fa', ''a", and 'la', three-syllable and three-sound word. The words, which will be studied, are used among speakers of Arabic, and have equivalents in Arabic, besides they follow Arabic rules in a variety of methods, syntactically, morphologically and phonetically. In the process of arabization, these words show that a change happens by an addition of a letter, deletion or replacement of a letter, or by a change in the manner of articulation. Moreover, they exist in more than one phonetic form which permits Arabic language to adopt one of these forms and arabize it.